Social policy in a Christian frame of meaning : a world-view, ethic and theoretical framework for the analysis, choice, & design of social policy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Policy, School of Sociology, Social Policy and Social Work, Massey University - Warner, Gerald John (Massey University, 2001)
This thesis is about how one might think, read, and approach, the analysis, choice, and design of social policy from a Christian world-view, ethic, and theoretical framework. This theoretical, normative, and explorative study is based on the propositions that all polities operate within some kind of frame of meaning, and that all social judgement is ultimately influenced by the presuppositions contained in one's broader world-view. In response, the thesis examines the Christian Realist, the Reformed/neo-Calvinist, and the Catholic social teaching traditions as contributors to the development of a Christian communitarian theoretical framework. Upon the exploration of the social, political, and moral theory, and the theological underpinnings of these three Christian traditions, this thesis approaches the theory eclectically focusing primarily on their mutually supportive aspects. The study finds a triangular relationship between the three traditions, such that each tradition supplements, informs, and complements the other. The Realist tradition maintains a consistent account of human nature and vitality, explicating human self-interest and power in social life, and thus appends both the Reformed and Catholic traditions. The Reformed tradition complements the Realist and substitutes Catholic social theory with a systematic theory of the structure of society. Moreover, the Catholic tradition provides the Reformed and Realist traditions with the systematic moral and ethical ends to which Christian social action ought to be orientated. The study also develops an approach to social policy indicative of the major ethos and orientation that characterises each tradition. The study therefore approaches the analysis of social policy from a responsible and realist frame of mind, recognising the plural nature of distinct spheres and jurisdictions within society, whilst maintaining a compassion for, and the centrality of, the human person. After orchestrating the theory into the construction of a Christian theoretical and normative frame, the study seeks to apply and utilise the Christian frame for the analysis, choice, and design of social policy. In response, the investigation examines a method for the inquiry of political frames of meaning (frame-critical policy analysis), employing the normative Christian communitarian frame as a counter-system. This policy analysis method dialectically critiques contesting policy viewpoints as grounded in their wider ideological social choice.
Keywords: New Zealand; Social policy; Philosophy; Church and social problems